Production of CoAl and CoAlCr FSMAs and determination of their thermal, microstructure, and magnetic properties - Malkoc, Turkan; Dagdelen, Fethi (Springer, 2019)
In this study, some thermal, mechanical, and magnetic properties of Co86Al14 and Co82Al14Cr4 (at.%) alloys have been investigated. The alloys were produced by arc melting method, and their thermal properties such as phase transformation temperature, enthalpy, and entropy were measured using differential scanning calorimetry (DSC). In addition, TG/DTA device has been utilized for determining Curie temperature for each sample. Furthermore, to specify crystal structure and microstructure of specimens, XRD and optical microscope techniques were used. In addition, Vickers hardness test as a mechanical property has been accomplished to compare the effect of Cr addition to CoAl-based shape memory alloy. Finally, at room temperature, physical property measurement system has been used to reveal magnetization of SMAs. The transformation temperatures obtained from DSC measurement at a heating rate of 20 A degrees C min(-1) for Co86Al14 (at.%) alloy were A (s) = 235.3 A degrees C, A (f) = 293.4 A degrees C, M (s) = 105.1 A degrees C, and M (f) = 56.9 A degrees C, while the same measurements for Co82Al14Cr4 (at.%) alloy gave A (s) = 295.1 A degrees C, A (f) = 333.4 A degrees C, M (s) = 166.5 A degrees C, and M (f) = 136.6 A degrees C, which showed a significant increase due to the incorporation of (4 at.%) of Cr. In contrast, the quantitative values of each enthalpy and entropy were diminished. Moreover, magnetization saturation values for the CoAl and CoAlCr shape memory alloys were determined by H-M measurements to be 127.23 and 107.06 emu g(-1), respectively, and their Curie temperature (T (C)) were 716.71 and 686.22 A degrees C, respectively. What is more, Vickers hardness values for the CoAl and CoAlCr alloys were measured to be 203.40 and 239.22 HV, respectively. Thus, the microhardness value increased remarkably for adding (4 at.%) of chromium to CoAl-based SMA.
Keywords: Ferromagnetic shape memory alloy (FSMA); Curie temperature; Austenite phase